SOPHE Computation on Alanine Single Crystal EPR Spectra - Frida U Ermawati (Universitas Negeri Surabaya, 2011)
Simulation of X-band first-derivative continuous-wave electron paramagnetic resonance (CW-EPR) experimental spectra of g-irradiated â„“-Î±-alanine single crystal has been carried out. The aim was to confirm the existence of radical induced by irradiation in the system. A SOPHE computer simulation software suite (v. 1.1.3) was utilized for that purpose. Six different X-band spectra measured from a number of defined crystal orientations to the external magnetic field B were recorded and simulated. The œaxial spectra (refer to the simulated spectra when the external B field was parallel to the crystal axes and that was measured at room temperature) confirm the simultaneous presence of the SAR, R2 and R3 radicals with the appropriate proportions. The œplanar spectra (refer to the simulated spectra when the B field was on the crystal planes), however, do not exactly fit to the experimental spectra. Together with the simulation outcomes, the problems that appear during the work, as well as the solutions proposed to overcome those problems are discussed.